Synthesis and detailed characterization of a newly synthesized chalcone, 3-(2,5-dimethoxyphenyl)-1-(naphthalen-2-yl)prop-2-en-1-one - Jayappa, Madhu Kumar Dogganal; Akhileshwari, Prabhuswamy; Sridhar, Mandayam Anandalwar; Nagarajappa, Lohith Tumakuru; Nagaraju, Shivegowda; Raghavendra, Subrayachar; Jayappa, Manasa Dogganal (European Journal of Chemistry, 2021)
Chalcones are the main component of some natural compounds. The title compound, 3-(2,5-dimethoxyphenyl)-1-(naphthalen-2-yl)prop-2-en-1-one, was synthesized and characterized. The compound (C21H18O3) crystallizes in the triclinic system with the space group of P-1 (no. 2), a = 7.7705(4) Å, b = 10.2634(6) Å, c = 11.2487(6) Å, α = 79.655(5)°, β = 81.500(5)°, γ = 68.039(5)°, V = 815.28(9) Å3, Z = 2, T = 293(2) K, μ(MoKα) = 0.086 mm-1, Dcalc = 1.297 g/cm3, 9126 reflections measured (4.318° ≤ 2Θ ≤ 52.728°), 3302 unique (Rint = 0.0466, Rsigma = 0.0528) which were used in all calculations. The final R1 was 0.0568 (I > 2σ(I)) and wR2 was 0.1667 (all data). The crystal structure is stabilized by both short C-H···O inter- and intra-molecular interactions. In addition, the crystal structure is reinforced by π-π interactions. Hirshfeld surface analysis confirmed the presence of C-H···O intermolecular interactions. The two-dimensional fingerprint plots are used to visualize the individual interactions present in the molecule. DFT calculations were performed to know the energy levels of the frontier molecular orbitals (HOMO-LUMO). The energy gap between the frontier molecular orbitals shows the kinetic stability of the molecule. The chemical reactive sites are observed by generating MEP surface. Non-covalent interactions (NCIs) are analyzed using reduced density gradient (RDG) analysis.